Bilateral lower second molar impaction in teenagers: An emergent problem? - Shinohara Elio; Kaba Shajadi; Pedron Irineu; Imparato Jose (Wolters Kluwer Medknow Publications, 2010)
The frequency of simultaneously impacted second and third molars in teenagers is increasing and becoming a common occurrence in adolescent oral surgery practice. The traditional treatment is the removal of the third molar by conventional access but repositioning of the surgical flap to the distal face of the first molar can predispose to complications such as pericoronitis and delayed healing of the attached gingiva. We present a case in which we use the germectomy approach to remove the impacted third molar for the eruption of the second molar through a vestibular incision. This incision offers excellent bone exposure and exit route for the third molar without disturbing the gingiva attached architecture on the distal face of the first molar providing good healing environment.